2012
DOI: 10.1038/cmi.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol attenuates the inflammatory response in asthma and decreases the pro-inflammatory cytokine secretion of dendritic cells

Abstract: Salmeterol is a long-acting b2-agonist that activates adenylate cyclase, causing long-lasting bronchodilation and has been used for many years to control asthma. However, little information is available about the immunoregulatory effects of salmeterol. We found that salmeterol decreases the production of pro-inflammatory cytokines in a model of allergen-challenged mice that expressed tumor-necrosis factor-alpha, interleukin-1 and interleukin-6. Dendritic cells (DCs) are antigen-presenting cells and act as sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Several reports showed that b 2 -AR stimulation mitigates NF-jB phosphorylation, nuclear translocation, DNA binding and transcriptional activity, in both immune (Farmer and Pugin, 2000;Herve et al, 2013;Hu et al, 2012;Loop et al, 2004;Loza et al, 2006;Mortaz et al, 2008;Strell et al, 2009;Yang et al, 2003) and non-immune cell types (Baouz et al, 2005;Yamaya et al, 2013) (For details refer to Table 1). In many cases NF-jB activity was measured via electrophoretic mobility shift assay (EMSA), which assesses DNA binding, or using microscopy to image NFjB localisation in the cell.…”
Section: Effects Of B 2 -Ar Modulators On the Activity Of Nf-jb Subunitsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several reports showed that b 2 -AR stimulation mitigates NF-jB phosphorylation, nuclear translocation, DNA binding and transcriptional activity, in both immune (Farmer and Pugin, 2000;Herve et al, 2013;Hu et al, 2012;Loop et al, 2004;Loza et al, 2006;Mortaz et al, 2008;Strell et al, 2009;Yang et al, 2003) and non-immune cell types (Baouz et al, 2005;Yamaya et al, 2013) (For details refer to Table 1). In many cases NF-jB activity was measured via electrophoretic mobility shift assay (EMSA), which assesses DNA binding, or using microscopy to image NFjB localisation in the cell.…”
Section: Effects Of B 2 -Ar Modulators On the Activity Of Nf-jb Subunitsmentioning
confidence: 98%
“…A large body of evidence suggests b 2 -AR triggering attenuates NF-jB via inhibition of IKK activity and/or upregulation of cellular IjBa levels (Farmer and Pugin, 2000;Gavrilyuk et al, 2001Gavrilyuk et al, , 2002Hu et al, 2012;Loop et al, 2004;Madrigal et al, 2006;Mortaz et al, 2008;Strell et al, 2009;Yang et al, 2010) (For details refer to Table 1). Here we will discuss in more detail a few studies in which a molecular mechanism was proposed.…”
Section: Effects Of B 2 -Ar Modulators On Ikk Activation and Ijb Levelsmentioning
confidence: 99%
“…Direct stimulation of macrophage and dendritic cell AR by NE also regulates inflammatory processes. High concentrations of NE that activate ß-AR inhibits proinflammatory cytokine production by macrophages and dendritic cells (Hu et al, 2012;Kees et al, 2003). Dendritic cell ß2-AR activation in vitro reduced pro-inflammatory cytokine IL-6, IL-12, and IL-23 production and elevated production of the anti-inflammatory cytokine, IL-10 (Hu et al, 2012;Nijhuis et al, 2014).…”
Section: A Inflammatory Reflexesmentioning
confidence: 99%
“…β 2 AR stimulation on both murine and human DCs reduced TLR-induced production of the inflammatory cytokines tumor necrosis factor-α (TNFα), IL-1 and IL-6 [104, 105], which was mediated partially by an inhibition of the NF-κB and MAPK signaling pathways [104]. β 2 AR stimulation on DCs also affected NOD2 signaling, along with its cross talk with TLR-2, resulting in cytokine production that favored a slant toward Th17 differentiation [106] and promoted Th2-associated inflammation [107].…”
Section: Introductionmentioning
confidence: 99%